2022
DOI: 10.1101/2022.08.09.503290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal transmission gives way to social transmission during gut microbiota assembly in wild mice

Abstract: The mammalian gut microbiota influences a wide array of phenotypes and is considered a key determinant of fitness, yet knowledge about the transmission routes by which gut microbes colonise hosts in natural populations remains limited. Here, we use an intensively studied wild population of wood mice (Apodemus sylvaticus) to examine how vertical (maternal) and horizontal (social) transmission routes influence gut microbiota composition throughout life. We identify independent signals of maternal transmission (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Consistent with the idea that maternal and social transmission may spread similar bacteria, our recent study on wood mice found that as young mice age, maternal transmission processes are gradually replaced by social transmission processes (65), with maternal and social effect in these mice both driven by microbes in the same family Muribaculaceae (35,65).…”
Section: Discussionsupporting
confidence: 66%
“…Consistent with the idea that maternal and social transmission may spread similar bacteria, our recent study on wood mice found that as young mice age, maternal transmission processes are gradually replaced by social transmission processes (65), with maternal and social effect in these mice both driven by microbes in the same family Muribaculaceae (35,65).…”
Section: Discussionsupporting
confidence: 66%
“…Cross‐fostering in this study took place at an early stage of life. For young mammals, vertical transmission of microbes is an important route of microbe colonization of the gut (Ferretti et al, 2018; Moeller et al, 2018; Wanelik et al, 2023). Potential effects of relatedness in our study could therefore be explained by both vertical transmission and host genotype.…”
Section: Discussionmentioning
confidence: 99%
“…To test the effects of spatial and temporal distances, species barriers, and hybridisation on the β-diversity of the intestinal community, we applied Bayesian generalised linear multilevel models using the Markov chain Monte Carlo algorithm No-U-Turn Sampler (NUTS) [54] implemented in Stan through the “brms” R package v. 2.19.0 [55]. The models had intestinal community similarity as the response, and we modelled all possible pairwise distances among mice (excluding comparisons between the same individuals) as previously described [31, 32]. We used a multimembership random effects framework that allows us to account for the individuals in each pairwise comparison (e.g., Individual A, Individual B).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, species composition as a response is a complex multivariate measure [30]. The analysis we present here is based on the realisation that effects on the community compositions can be tested elegantly using pairwise differences between samples as response (beta-diversity) and accounting for repeated comparisons using random effects in Bayesian multilevel models [31, 32]. These models require the predictor variables to be expressed in the same way as the response, as distances or other measures reflecting a compared pair.…”
Section: Introductionmentioning
confidence: 99%